ChemInform Abstract: New μ‐SnTe4 and μ‐Sn2Te6 Ligands to Transition Metal: Solvothermal Syntheses and Characterizations of Zinc Tellurostannates Containing Polyamine Ligands. Issue 33 (19th August 2014) - Lu, Jialin; Wang, Fang; Shen, Yali; Tang, Chunying; Zhang, Yong; Jia, Dingxian
Abstract Compounds (IV)—(VII) are solvothermally synthesized in the presence of iodide ions.